f ( x ) = 5 x 1 3 + 1 3 x 5 + 9 a x
Find the least positive integer a such that 65 divides f ( x ) for every integer x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Typos in 3th line: One has to write (mod 13) instead of mod (5) Apart from that: Solution is very elegant.
The same exact way
It suffices to tackle the problem m o d 6 5
When x = 1 we want 5 + 1 3 + 9 a ≡ 0 m o d 6 5 ⟺ 9 a ≡ − 1 8 m o d 6 5 which is a linear modular equation, so it has unique solution − 2 . Another way to obtain this is multiplying both sides by the inverse of 6 5 which is 2 9 to get a ≡ − 5 0 4 ≡ − 2 m o d 6 5
So if there is a solution it is − 2 . Lets see 5 x 3 + 1 3 x − 1 8 x ≡ 0 m o d 6 5 for every value of x , so that − 2 is indeed a solution.
It suffices to verify it m o d 1 3 and m o d 5 .
To see it m o d 5 notice 5 x 1 3 + 1 3 x 5 − 1 8 x ≡ 3 x 5 − 3 x ≡ 3 x − 3 x ≡ 0 m o d 5 by fermat's little theorem.
To see it m o d 1 3 notice 5 x 1 3 + 1 3 x 5 − 1 8 x ≡ 5 x 1 3 − 5 x ≡ 5 x − 5 ≡ 0 m o d 1 3 by fermat's little theorem.
This concludes the proof. Notice that Instead of using fermat we could check the 5 possible values of x m o d 5 and the 1 3 possible values of x m o d 1 3 . In any case we have the solution m o d 6 5 is − 2 , and the smallest positive integer in this congruence class is 6 3 , the answer.
Satyajit Mohanty, Please check wether my solution is right or wrong.
If f ( x ) is divisible by 65 then it should be divisible by f ( 1 ) (given). Now the result would be 1 8 + 9 a for f ( 1 ) .
6 5 ∣ 1 8 + 9 a = 6 5 ∣ 9 ( 2 + a )
Now 9, is not divisible by 65 therefore 2 + a = 6 5 n for minimum we will take n=1 2 + a = 6 5 a = 6 3
Please correct your slip....n=1 , 2 + a = 6 5 a = 6 3
Write a comment or ask a question...
Sadly, I did it the same way. Is there a more concrete method to this?
You didn't show that when a = 6 3 , f ( x ) is divisible by 6 5 for every x ∈ Z . You showed that this is the case just for x = 1 .
Problem Loading...
Note Loading...
Set Loading...
we have x 1 3 = x ( m o d 1 3 ) , x 5 = x m o d 5 because of FLT 5 x 1 3 + 1 3 x 5 + 9 a x = 3 x + 4 a x ( m o d 5 ) = ( 3 + 4 a ) x ( m o d 5 ) -> a = 3 mod 5 5 x 1 3 + 1 3 x 5 + 9 a x = 5 x + 9 a x ( m o d 5 ) = ( 5 + 9 a ) x ( m o d 5 ) -> a = 11 mod 13
combining, a = 63 mod 65 , a = 63